2011
DOI: 10.1016/j.ydbio.2010.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylation- and glycosylation-dependent functions of Skp1 in O2-regulated development of Dictyostelium

Abstract: O2 regulates multicellular development of the social amoeba Dictyostelium, suggesting it may serve as an important cue in its native soil environment. Dictyostelium expresses an HIF〈-type prolyl 4-hydroxylase (P4H1) whose levels affect the O2-threshold for culmination implicating it as a direct O2-sensor, as in animals. But Dictyostelium lacks HIF〈, a mediator of animal prolyl 4-hydroxylase signaling, and P4H1 can hydroxylate Pro143 of Skp1, a subunit of E3SCFubiquitin-ligases. Skp1 hydroxyproline then becomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…FLAG-FbxD Delays Development in an F-box-and Glycosylation-dependent Fashion-Previous studies showed that disruption of phyA delays developmental progression, mainly at the culmination stage (transition from slug to fruiting body), by ϳ3 h at 21% O 2 (14). Our novel findings suggested that the underlying mechanism might be an O 2 -and prolyl-hydroxylation-regulated interaction with FbxD and FbxA.…”
Section: Figmentioning
confidence: 49%
See 3 more Smart Citations
“…FLAG-FbxD Delays Development in an F-box-and Glycosylation-dependent Fashion-Previous studies showed that disruption of phyA delays developmental progression, mainly at the culmination stage (transition from slug to fruiting body), by ϳ3 h at 21% O 2 (14). Our novel findings suggested that the underlying mechanism might be an O 2 -and prolyl-hydroxylation-regulated interaction with FbxD and FbxA.…”
Section: Figmentioning
confidence: 49%
“…However, no significant proteins interactors were detected, despite the utility of this construct in yeast (37). Interestingly, we previously noted that FLAG-Skp1 remains unmodified when expressed in Dictyostelium (14), indicating that perturbation of its N terminus interferes with not only its ability to enter SCF complexes, but also its hydroxylation and glycosylation.…”
Section: Figmentioning
confidence: 93%
See 2 more Smart Citations
“…In Dictyostelium, biochemical studies indicate that Skp1 is the only substrate for the orthologs of these GTs, and disruption of either gnt1 or pgtA inhibits development in a way that is related to, but less severe than, disruption of phyA (10). Gene dosage manipulations on Skp1 expression show inverse effects on development consistent with the modification genes acting via Skp1 in this organism, a model that is supported by point mutations that remove the target Pro residue, and from a double mutant between a GT gene and one of two Skp1 genes (23). By analogy, and based on similar phenotypes of TgphyA⌬ and Tggnt1⌬, we propose that the modification genes render their effects in a common pathway that affects Skp1.…”
Section: Discussionmentioning
confidence: 62%